Aerobic Exercise Reduces Asthma Phenotype by Modulation of the Leukotriene Pathway - Alberca-Custódio, Ricardo Wesley; Greiffo, Flávia Regina; MacKenzie, BreAnne; Oliveira-Junior, Manoel Carneiro; Andrade-Sousa, Adilson Santos; Graudenz, Gustavo Silveira; Santos, Angela Batista Gomes; Damaceno-Rodrigues, Nilsa Regina; Castro-Faria-Neto, Hugo Caire; Arantes-Costa, Fernanda Magalhaes; Martins, Milton De Arruda; Abbasi, Asghar; et al. (Frontiers in Immunology, 2016)
Introduction: Leukotrienes (LTs) play a central role in asthma. Low to moderate intensity aerobic exercise (AE) reduces asthmatic inflammation in clinical studies and in experimental models. This study investigated whether AE attenuates LT pathway activation in an ovalbumin (OVA) model of asthma. Methods: Sixty-four male, BALB/c mice were distributed into Control, Exercise (Exe), OVA and OVA+Exe groups. Treadmill training was performed at moderate intensity, 5x/week, 1hr/session for 4 weeks. Quantification of bronchoalveolar lavage (BAL) cellularity, leukocytes, airway remodeling, interleukin (IL) IL-5, IL-13, leukotriene Cys (CysLT) and leukotriene B4 (LTB4) in BAL was performed. In addition, quantitative analyses on peribronchial leukocytes and airway epithelium for LT pathway agents: 5-lypoxygenase (5-LO), LTA4 hydrolase (LTA4H), CysLT1 receptor, CysLT2 receptor, LTC4 synthase, and LTB4 receptor 2 (BLT2) were performed. Airway hyperresponsiveness to methacholine was assessed via whole body plethysmography. Results: AE decreased eosinophils (p<0.001), neutrophils (p>0.001), lymphocytes (p<0.001) and macrophages (p<0.01) in BAL, as well as eosinophils (p<0.01), lymphocytes (p<0.001) and macrophages (p>0.001) in airway walls. Collagen (p<0.01), elastic fibers (p<0.01), mucus production (p<0.01) and smooth muscle thickness (p<0.01), as well as IL-5 (p<0.01), IL-13 (p<0.01), CysLT (p<0.01) and LTB4 (p<0.01) in BAL were reduced. 5-LO (p<0.05), LTA4H (p<0.05), CysLT1 receptor (p<0.001), CysLT2 receptor (p<0.001), LTC4 synthase (p<0.001) and BLT2 (p<0.01) expression by peribronchial leukocytes and airway epithelium were reduced. Lastly, airway hyperresponsiveness to methacholine 25mg/mL (p<0.05) and 50mg/mL (p<0.01) was reduced. Conclusions: Moderate intensity AE attenuated asthma phenotype and leukotriene production in both pulmonary leukocytes and airway epithelium of OVA-treated mice.